Date rape among Cypriot female college students: an explorative study - Kouta, Christiana; Tolma, Eleni L.; Pavlou, Susana Elisa (My University, 2013)
This study examined the prevalence and reporting of date rape among female college students (aged 18-24) in Cyprus and assessed the students' attitudes and awareness regarding date rape. In addition, the study examined how date rape is perceived among representatives of related private and governmental organizations in Cyprus. This is part of a larger multi-country study. This paper will focus only on the results pertaining to Cyprus. The study was coordinated by the Mediterranean Institute of Gender Studies. This study used quantitative and qualitative methods. In total, 476 female college students responded to an anonymous questionnaire, two focus group discussions were carried out, and five key-informant interviews with relevant institutional representatives were conducted. The results of the study indicated that unwanted sexual experiences and sexual violence, including date rape, do exist among young Cypriot women. Specifically, 1.3% of the research participants reported experiencing an attempted rape by their date, and 1.9% of the study participants reported being raped on a date. Often this was caused by their boyfriend, friend or sexual partner (54.2%). The results of the qualitative study showed that young female Cypriots agreed that many women give in to psychological pressure because they feel guilty about letting the other person down or because they 'didn't satisfy him' or fear they might lose him. Despite the explorative nature of the study, it is significant as research on date rape in Cyprus is almost non-existent. The authors anticipate that the results of the study will be useful to other researchers and policy-makers involved in this area of research.
Keywords: Date rape; Female; Unwanted sexual experiences; Violence